PENGUKURAN RISIKO PADA PENERAPAN CLOUD COMPUTING UNTUK SISTEM INFORMASI (STUDI KASUS UNIVERSITAS BINA DARMA) - Ria Andryani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
College is an academic organization, an institution which has a role and strategic position in the achievement of educational goals. To achieve The goal, the college needs the support of information technology in carrying out its activities. There are currently utilizing cloud computing technology be one solution to optimize operational effectiveness and efficiency information technology in higher education. However, the use of new technologies of potential risks in their operations that have an impact on performance organization. Therefore we need appropriate risk management for implementation cloud computing in order to improve the performance of colleges. Research It aims to measure the level of possible risks arising from the introduction cloud computing at the university to make use of the OCTAVE Framework on the application of cloud computing technology for information systems at universities high (Bina Darma University case study). This research resulted in the level of University information system readiness Bina Darma in applying technology cloud computing that are in a position YELLOW, namely the implementation of the information system has supported the adoption of cloud computing, but more needs to be improved.